PENDAMPINGAN PASTORAL KONSELING PADA PELAYAN GEREJA DALAM MENGATASI BURNOUT - Patricia Gebriela Gagola; Yohan Brek (PT. GIAT KONSELING NUSANTARA, 2024)
Church ministry often demands high commitment and dedication, which can lead to burnout in church ministers. Burnout is a condition of physical, emotional, and mental exhaustion due to prolonged stress that impacts performance and personal well-being. This study aims to examine the importance of pastoral counseling assistance in helping church ministers overcome burnout. The method used is a case study with a qualitative approach through interviews with church ministers who experience burnout. The results showed that a pastoral counseling approach based on spiritual healing, and an empathic emotional approach can provide significant support for church ministers to overcome burnout. In addition, the importance of the role of pastoral assistants who provide space for church ministers to talk, reflect, and accelerate the recovery process. This study suggests that churches pay more attention to the mental and spiritual health of church ministers through structured and sustainable mentoring programs to maintain the balance of their lives in carrying out ministerial duties.